Exploring the Employment Experiences of People with Physical Disabilities in Vietnam: Towards Inclusive Workplaces - Hien Nguyen; June Alexander; Michelle Bellon (Disabilities)
Despite advancements in legal protections for people with disabilities in Vietnam, significant barriers to employment persist. This qualitative phenomenological study explored the employment experiences of people with physical disabilities in Vietnam. Semi-structured interviews with 15 participants employed across different sectors were thematically analysed, with the ecological systems theory applied as a guiding framework to interpret the findings and implications. Three primary themes were revealed: accessibility, vulnerability, and discrimination and ableism. The results also emphasised the importance of positive attitudes and interactions from co-workers and supervisors in fostering inclusive workplaces. Recommendations include policy reforms for attitudinal shifts, focus on equity to improve workplace culture, and the involvement of people with disabilities in organisational decision making. These actions are essential for creating more diverse and inclusive workplaces in Vietnam, where employees with physical disabilities feel included, valued, and empowered.